Minhāj al-wilāya fī sharḥ Nahj al-balāgha. Volume 1 - Tabrīzī, ʿAbd al-Bāqī Ṣūfi (Miras Maktoob, ISBN: 9789004365452., 2019)
The Nahj al-balāgha is a collection of sermons, letters, testimonials, and wise sayings attributed to ʿAlī b. Abī Ṭālib (d. 40/661), the Prophet's son-in-law, successor, and first imam of the Shīʿa. The collection was compiled by al-Sharīf al-Raḍī (d. 406/1088), a distinguished ʿAlid member of Baghdad's ruling elite. The Nahj al-balāgha is widely considered as a work of extraordinary literary quality, besides being an invaluable source of information on the person, opinions, and virtues of ʿAlī. Many commentaries on it were written, in Arabic and in Persian. The present, two-volume Persian commentary was written by ʿAbd al-Bāqī Ṣūfī Tabrīzī (d. 1039/1629-30), who spent most of his active life in then-Ottoman Baghdad, mystics mostly having a hard time under the Safavid ruler Shāh ʿAbbās I (r. 1587-1629). The commentary is thematically organized into twelve sections and explains the text from a variety of angles, with discussions ranging from theology and tradition to philosophy and mysticism. 2 vols; volume 1.